2017
DOI: 10.1021/jacs.7b05807
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an Antiaromatic Singlet Cyclopentadienyl Zwitterion

Abstract: The reaction of triplet tetrachlorocyclopentadienylidene with BF in rare gas matrices yields a zwitterion consisting of a cyclopentadienyl cation bearing a positive charge and a negatively charged BF unit. IR and UV-vis spectra as well as the absence of EPR signals demonstrate a singlet ground state of the zwitterion, and its calculated geometry and magnetic properties clearly reveal a strong antiaromatic character. The zwitterion is highly labile and by visible or IR irradiation rearranges via a 1,2-fluorine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…The ACID plot for 3 CpCl 5 + + is consistent with that by Sandera nd co-workers, who calculated aN ICS(0) value of À2.4 ppm, indicating moderate aromatic character. [65] We now performed a NICS scan to quantify the Baird-aromaticity of 15(H) 2 2 + + in its T 0 state. The minimum value along the NICS-Z scan for the T 0 state of 15(H) 2 2 + + (À13.8 ppm) is closet ot hat of 3 CpCl 5 + + (À14.3 ppm), indicating that the two species are approximately equallyB aird-aromatic.…”
Section: Resultsmentioning
confidence: 99%
“…The ACID plot for 3 CpCl 5 + + is consistent with that by Sandera nd co-workers, who calculated aN ICS(0) value of À2.4 ppm, indicating moderate aromatic character. [65] We now performed a NICS scan to quantify the Baird-aromaticity of 15(H) 2 2 + + in its T 0 state. The minimum value along the NICS-Z scan for the T 0 state of 15(H) 2 2 + + (À13.8 ppm) is closet ot hat of 3 CpCl 5 + + (À14.3 ppm), indicating that the two species are approximately equallyB aird-aromatic.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the ground state of 1 is switched from triplet to singlet.T his is not only observed in cryogenic matrices at low temperature, [10,11] but also in solution at room temperature. [12] Carbene 2 shows as imilar behavior, [13] whereasi n3 the singlet-triplet splitting is too large to be overcome by hydrogen bonding.H alogen bondings tabilizes the singlet stateso fc arbenes even more than hydrogen bonding, [14] and BF 3 formss tronglys tabilizedd onor-acceptor complexes, [15,16] similart oN H 3 -BF 3 .T hese resultss tress the high basicity of the closed-shell singlet stateso fc arbenes.…”
Section: Introductionmentioning
confidence: 89%
“…Carbene 2 shows a similar behavior, whereas in 3 the singlet‐triplet splitting is too large to be overcome by hydrogen bonding. Halogen bonding stabilizes the singlet states of carbenes even more than hydrogen bonding, and BF 3 forms strongly stabilized donor‐acceptor complexes, similar to NH 3 ‐BF 3 . These results stress the high basicity of the closed‐shell singlet states of carbenes.…”
Section: Introductionmentioning
confidence: 99%
“…The classic methods for trapping singlet carbenes when the stability is not yet known or as proof of formation for non isolable derivatives are the condensations of the carbene with elemental sulfur, selenium, or CS 2 . The latter can be particularly informative as, in addition to a diagnostic infrared absorbance, complexation of CS 2 provides an additional 13 C NMR handle that is often useful for characterization purposes, is frequently accompanied by an intense color change, and affords an inner salt for which the difference in solubility may facilitate isolation [5]. As with CS 2 , the addition of carbon dioxide, isothiocyanates, isocyanates, and ketenes results in a new C-C bond and the formation of an inner salt with the positive charge at the carbene carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Another aspect that we will not systematically discuss is the existence of carbenes in two forms, the singlet and the triplet. The singlet-triplet gap [6,7], when not very large [8], can be modified by complexation a situation mainly studied by Sander [9][10][11][12][13]. In this review we will specify the multiplicity when reported.…”
Section: Introductionmentioning
confidence: 99%